Factors That Shape The Decision to Have a Boarding House at Bu Tin's Boarding House in West Surabaya - Linardo, Wilson (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The definition of boarding house is a type of rental room that is rented for a certain period of time in accordance with the room owner’s agreement and the agreed price. High demand for boarding house in West Surabaya led to higher boarding house competition. By knowing factors that influence consumer’s purchasing decision could help Bu Tin’s boarding house withstand in the competition and increase occupancy rate. The results obtained are that exploratory factor analysis can be used to determine considered factors in determining factors that influence consumer’s purchasing decision. It is based on eigen value of seven factors that has value more than one. The formed factors were insurance, mobility, property design & layout, property facility, service convenience, curfew flexibility, price.